PENGARUH FINANCIAL TECHNOLOGY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR TENAGA KERJA MILENIAL KOTA PADANG - Annisa Nabila Putri; Friyatmi Friyatmi (Jurnal Kompetitif, 2023)
The purpose of this research is to analyze the effect of financial technology on the financial management behavior of the millennial workforce in Padang City. This type of quantitative research with a comparative causal research design. The primary data source was obtained by distributing questionnaires using the Google form to the research sample. The research sample was determined using a purposive sampling technique of 100 respondents. Data were analyzed using a simple linear regression technique with the help of the SPSS 26 program. The results of the study revealed that Financial Technology on the Financial Management Behavior of the Padang City millennial workforce. Abstrak Tujuan dari penelitian ini adalah untuk menganalisis pengaruh financial technology terhadap financial management behavior tenaga kerja milenial Kota Padang. Jenis penelitian kuantitatif dengan desain penelitian kausal komparatif. Sumber data primer didapatkan melalui penyebaran kuesioner menggunakan google form kepada sampel penelitian. Sampel penelitian ditentukan menggunakan teknik purposive sampling sebanyak 100 responden. Data dianalisis menggunakan teknik regresi linier sederhana dengan bantuan program SPSS 26. Hasil penelitian mengungkapkan bahwa Financial Technology terhadap Financial Management Behavior tenaga kerja milenial Kota Padang.